2003
DOI: 10.1111/1467-6494.7103007
|View full text |Cite
|
Sign up to set email alerts
|

Two Spheres of Belief in Justice: Extensive Support for the Bidimensional Model of Belief in a Just World

Abstract: The purpose of this research comprising five studies (N 5 666) was to further corroborate the bidimensional conceptualisation of the belief in a just world proposed by . It was demonstrated that belief in a just world for the Self (and not for Others) was correlated to evaluations of the meaning of life. Belief in a just world for Others was significantly correlated to discrimination against the elderly, stigmatisation of poverty, and higher penal punitiveness, while belief in a just world for Self was weakly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
5
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 85 publications
(100 reference statements)
9
151
5
16
Order By: Relevance
“…Although both kinds of BJW, as measured by scales, tend to be positively correlated (e.g. Dalbert, 1999), Bègue and Bastounis (2003) have empirically confirmed the conceptual distinction between these two kinds of BJWs which are seen as two spheres of belief in justice. In fact, empirical studies have shown that the personal BJW is a better predictor of well-being than the general BJW (e.g., Dzuka & Dalbert, 2002) and that the general BJW is a better predictor of reactions to victims (e.g., Sutton & Douglas, 2005).…”
Section: Goals and Overviewmentioning
confidence: 92%
“…Although both kinds of BJW, as measured by scales, tend to be positively correlated (e.g. Dalbert, 1999), Bègue and Bastounis (2003) have empirically confirmed the conceptual distinction between these two kinds of BJWs which are seen as two spheres of belief in justice. In fact, empirical studies have shown that the personal BJW is a better predictor of well-being than the general BJW (e.g., Dzuka & Dalbert, 2002) and that the general BJW is a better predictor of reactions to victims (e.g., Sutton & Douglas, 2005).…”
Section: Goals and Overviewmentioning
confidence: 92%
“…For example, researchers, such as Lipkus, Dalbert and Siegler (1996) suggest that it is beneficial to construct the multidimensional aspect of individuals' beliefs about what is just, and they made a distinction between BJW for self and BJW for others or in general. Using this multidimensional BJW scale, Bègue and Bastounis (2003) found that the BJW for others scale was significantly correlated to discrimination and stigmatization of others, while the BJW for self was weakly or not related to these variables. Therefore, in order to examine the observer's attitude toward alleged rape victim, the BJW for others scale was used in this study.…”
Section: Rape Scenariosmentioning
confidence: 97%
“…They tend to derogate the victim, such as prejudice against the poor and/or unemployed, the elderly, prisoners, the severely ill, patients with neuroses, immigrants, etc. (Begue & Bastounis, 2003;Bizer, Hart, & Jekogian, 2012;Kestner, 2009). Similarly, BJW people tend to believe that good fate persons deserve their good outcomes because of previous good actions.…”
Section: Dual-process Cognitions (Dpc)mentioning
confidence: 99%